2014
DOI: 10.1177/000313481408000830
|View full text |Cite
|
Sign up to set email alerts
|

Moped Collisions among Patients with Revoked Drivers’ Licenses are a Significant Public Health Problem: A Retrospective Cohort Study

Abstract: Many states do not require a license to operate a moped, defined as a motor vehicle with less than 50-cc engine displacement. These vehicles may therefore serve as a mode of transportation for those who are driving without a license and who may have a history of prior high-risk behavior. We hypothesized that those involved in moped collisions were more likely to have previous convictions for driving while intoxicated (DWI) and other non-DWI offenses than those on conventional motorcycles. At a Level I trauma c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…15,16 In some studies, almost half of MP drivers involved in motor vehicle crashes had a history of driving a car or MC under the influence of alcohol. 17,18 In many countries, traffic conditions may limit the top speed MPs can achieve in This study was presented as a poster at the annual meeting of the Southeastern Surgical Congress, February 20-23, 2016 in Atlanta, GA.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 In some studies, almost half of MP drivers involved in motor vehicle crashes had a history of driving a car or MC under the influence of alcohol. 17,18 In many countries, traffic conditions may limit the top speed MPs can achieve in This study was presented as a poster at the annual meeting of the Southeastern Surgical Congress, February 20-23, 2016 in Atlanta, GA.…”
Section: Introductionmentioning
confidence: 99%
“…It can be speculated that lower rates of employment and health insurance may be related to their higher rate of criminality and alcohol abuse, as previously noted. 3 Injury patterns differed between the groups, including higher rates of head injuries in moped drivers. We theorize that this difference may be because of disparity in helmet use, though that data were unavailable.…”
mentioning
confidence: 97%
“…The lack of regulation provides a legal mode of transportation for operators who have had their driver's licenses rescinded for a variety of reasons, including previous driving while intoxicated or other criminal charges. 3 Although previous investigations have analyzed injury patterns in motorcycle crashes, there has been limited evaluation of moped crashes, which involve passengers who are less regulated than motorcyclists. Our hypothesis in the current investigation is that there are significant differences between moped and motorcycle drivers involved in crashes.…”
mentioning
confidence: 99%
“…The limited literature on moped collision risk factors highlights the influence of alcohol and lack of licensing. In a cohort study of North Carolina emergency room admissions records, admitted patients from moped collisions had a relative risk of 4.8 of having a DWI (driving while intoxicated) compared with that of admitted motorcycle operators ( 4 ). In a review of Florida crash incidents, moped operators who were found to have consumed alcohol had a relative risk of 2.09 of experiencing a severe crash versus a non-severe crash ( 5 ).…”
mentioning
confidence: 99%